Competitive Removal of Perchlorate Ions by Quaternary Amine Modified Reed in the Presence of Nitrate and Phosphate - Salem Baidas; Khaled Al-Deyain; Xiaoguang Meng; Baoyu Gao (Adsorption Science & Technology)
We report a kinetic and equilibrium study in which we examined the removal of perchlorate anions from water by adsorption onto modified reed (MR), an adsorption material constituted by giant reed (GR) particles whose anion adsorption properties have been enhanced by quaternary amine (QA) crosslinking. In particular, we examined how MR adsorption of perchlorate interacts competitively with concomitant adsorption of agriculture-derived phosphate and nitrate contaminants. Equilibrium and pH experiments were first conducted in single-component systems, the results of which were best described by the Langmuir-Freundlich (L-F) isotherm. Subsequent analyses of competitive effects on adsorption showed that although MR had a higher adsorption capacity for perchlorate alone than for nitrate or phosphate alone, the addition of either phosphate or nitrate to a perchlorate solution had a diminishing effect on MR adsorption of perchlorate within a natural-water pH range, with phosphate having the stronger competitive effect. Perchlorate adsorption on MR varied inversely with competing ion concentrations, providing direct evidence of the perchlorate diminution effect being attributable to anion competition. Finally, we developed a multicomponent isotherm model that describes the binary adsorption of perchlorate in the presence of each of these competing anions. The results of this work provide perchlorate removal efficiency information that is directly applicable to the design of water treatment systems.